Heat and Mass Transfer Analysis on MHD Jeffrey Fluid Flow Past a Vertically Inclined Plate in Presence of Magnetic Field and Double Diffusive Effects - Y. Sunita Rani, P Suresh, M V Ramana Murthy (International Journal of Advanced Science and Technology, 2020)
A numerical ideal is developed toward learning the double diffusive belongings on magneto hydrodynamic incompressible, viscous, electrically directing Jeffrey liquid concluded a vertically motivated plate in the occurrence viscous dissipation, warmth in addition to mass transmission. Non-dimensional quantities remain used to translate the governing non-linear in completed inference equations to a set of coupled linear partial discrepancy calculations. The resulting equations remain then answered mathematically by limited modification method. The influence of numerous dimensionless limitations on the speed, hotness also deliberation distributions remain analyzed too discussed through graphs as fine as the mathematical standards of Skin-friction constant, Nusselt also Sherwood numbers discussed over tables. Subsequently the present results remain in very good arrangement through the results obtained for a viscous fluid.